(3GdfXGe GdbGfhfj dJCSjS TQcI GdeSGgeI (B/s - (3YHO GdbGOQ, MeQ GdYjfs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdLGeYI GdLOjOI ddWHGYI hGdfTQ hGdJhRjY,s, 2013)
(3jJfGhd cJGH (B((3GdfXGe GdbGfhfj dJCSjS TQcI GdeSGgeI(B) (3hGdPj bGe HJCdjag MeQ GdYjf YHO GdbGOQ aj MhGdj (B(185) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdTQcGJ GdeSGgeI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3ELQGAGJ GdJCSjS, GdeHMK GdChd (B: (3GdCQcGf GdehVhYjI, GdeWdH GdChd (B: (3GdCQcGf GdehVhYjI GdYGeI, GdeHMK GdKGfj (B: (3GdCQcGf GdTcdjI ddJCSjS, GdeWdH GdChd (B: (3GdJCSjS GdeJJGHY Ch HGddLhA Edi GdEONGQ GdYdfj, GdaUd GdKGfj (B: (3LRGA eNGdaI ELQGAGJ GdJCSjS, GdeHMK GdChd (B: (3GdHWdGf, GdeWdH GdChd (B: (3GdHWdGf GdeJQJH hab GdbhGYO GdYGeI, GdeHMK GdKGfj (B: (3GdeSDhdjI GdeOfjI hGdLRGFjI, GdeWdH GdChd (B: (3GdeSDhdjI GdeOfjI, NGJeI, Ke jfJgj HbGFeI GdeUGOQ(B. s
(3HHdjhLQGajI (B: (3UaMI (B177-182.s
Keywords: (3GdTQcGJ GdeSGgeIs -- (3bhGfjf hJTQjYGJs -- (3GdLRGFQs; (3GdTQcGJs -- (3bhGfjf hJTQjYGJs -- (3GdLRGFQs